PWM control techniques for three phase three level inverter drives - Arkan A. Kadum (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
In this paper two very efficient pulse width modulation techniques were discussed named Sin pulse width modulation and space vector pulse width modulation. The basic structure of the three-level inverter neutral-point clamped is introduced and the basic idea about space vector pulse width modulation for three-level voltage source inverter has been discussed in detail. Nearest three vectors space vector pulse width modulation control algorithm is adopted as the control strategy for the three phase three level NPC inverter in order to compensate the neutral-point shifting. Mathematical formulation for calculating switching sequence has determined. Comparative analysis proving superiority of the space vector pulse width modulation technique over the conventional pulse width modulation, and the results of the simulations of inverter confirm the feasibility and advantage of the space vector pulse width modulation strategy over sin pulse width modulation in terms of good utilization of dc-bus voltage, low current ripple and reduced switching frequency. Space vector pulse width modulation provides advantages better fundamental output voltage and useful in improving harmonic performance and reducing total harmonic distortion.